Kinetics and Mechanism of the Oxidation of Menthol by Potassium Bromate in Acidic Solution - na, Ravikant; Meena, Ms.; Sharma, Shrikant (International Journal of Pharmacological Research, 2014)
No suitable method is available for the estimation of menthol, hence in all kinetic results reported in this chapter, menthol was in excess over potassium bromate and the stoichiometry was also determined under the experimental conditions where menthol (substrate) was in excess over potassium bromate (oxidant). Present study was focused on the analysis of kinetics and mechanism of oxidation of neomenthol by potassium bromate in acidic medium. For oxidizing neomenthol, potassium bromate stock solution (5.00 ?2 mol. dm ?3 ) was prepared by dissolving exactly weighed quantity of potassium bromate in doubly distilled water. The suitable reaction mixtures were prepared and left at 313 K for over 24 hours to ensure complete oxidation of neomenthol. The unreacted potassium bromate was determined iodometrically and the results indicate that one mole of potassium bromate is consumed for every three moles of neomenthol and leads to the formation of menthone (ketone).